HUBUNGAN KEYAKIANAN DIRI (SELF EFFICACY) DENGAN PRESTASI BELAJAR MAHASISWA D-III KEBIDANAN TINGKAT 1I DI UNIVERSITAS BATAM TAHUN 2017 - Sofhiani, Risqi Eka; Utami, Risqi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Self-efficacy (self-efficacy) is closely related to learning achievement. If a person has high self efficacy, he can rely on his ability to achieve high learning achievement. This study aims to determine the relationship between self efficacy with the achievement of D-III midwifery level II, Research conducted in April-July 2017 at the University of Batam. The population is a graduate student of II-grade obstetrics at the University of Batam. Sample of this research is total sampling amounted to 38 respondents. Result of research, from 38 students who have high self efficacy with very satisfying learning achievement as much as 33 people (86,8%) when seen from chi-square test got Ï-value <0,05. It can be concluded there is a relationship between self-confidence (self efficacy) with the achievement of D-III students of midwifery level II. The next research is expected to add the number of self-efficacy variables, learning achievement variables, the number of rsponden and a better place for new research to compare results.